2018
DOI: 10.2224/sbp.6561
|View full text |Cite
|
Sign up to set email alerts
|

Within-culture variation in field dependence/independence: A region-level investigation across China

Abstract: Field dependence/independence (FDI), refers to one's preferred style in perceiving one's surroundings, either analytically and individually, or globally and collectively, and has been a popular topic in recent cross- and within-culture research. Previous researchers have suggested that members of individualist and collectivist cultures differ in the degree to which they perceive objects either analytically and context-independently or holistically and context-dependently. Cross-culture variation in FDI has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Recently, a series of studies ( Talhelm et al, 2018 ; Xu and Xin, 2019 ; Zhu et al, 2019 ; see Talhelm, 2020 , for a review) have confirmed and manifested the north-south difference in China. Consistent with the north-south regional distribution of psychological differences are other research findings on individualism and collectivism ( Ma et al, 2016 ) and field-dependence and -independence ( Peng et al, 2018 ). Together, these studies point to a northern Chinese cultural-cognitive system featuring analytic and field-independent cognitions, independent self-construal, and individualism; and a southern Chinese cultural-cognitive system featuring holistic and field-dependent cognitions, interdependent self-construal, and collectivism.…”
Section: Introductionsupporting
confidence: 79%
See 4 more Smart Citations
“…Recently, a series of studies ( Talhelm et al, 2018 ; Xu and Xin, 2019 ; Zhu et al, 2019 ; see Talhelm, 2020 , for a review) have confirmed and manifested the north-south difference in China. Consistent with the north-south regional distribution of psychological differences are other research findings on individualism and collectivism ( Ma et al, 2016 ) and field-dependence and -independence ( Peng et al, 2018 ). Together, these studies point to a northern Chinese cultural-cognitive system featuring analytic and field-independent cognitions, independent self-construal, and individualism; and a southern Chinese cultural-cognitive system featuring holistic and field-dependent cognitions, interdependent self-construal, and collectivism.…”
Section: Introductionsupporting
confidence: 79%
“…Validity was tested by correlating the EFT with the Rod-and-Frame test ( r = 0.49, p < 0.05). Peng et al (2018) has already applied the test to their survey and developed clear instructions on how to perform the task, which was in line with previous studies (e.g., Hao et al, 2013 ). In the present experiment, participants had to complete as many of the nine tasks in each session within 4 min, which was timed to suit university students.…”
Section: Methodssupporting
confidence: 64%
See 3 more Smart Citations